A Computer Assembly Training With VR Technology - Tanadon Parosin; Sittijet Vanichsan; Pornsuree Jamsri (My University, 2024)
This article discusses the creation and development of a learning platform called "RookiePC". This learning platform serves as a guide for users on how to assemble a computer, aiming to reduce errors and resource usage in the assembly process. It will present the development process of the learning platform and user evaluation after usage. This learning platform is developed with VR technology via Oculus Quest 1 and the Unreal Engine software. RookiePC is designed as an educational simulation game to inspire learners about computer components and its assembly knowledge. This platform offers 2 modes: 1) Learning Mode, which provides basic knowledge of 11 essential components and the steps involved in assembling a computer including embedded tips and insights; and 2) Practice Mode, which allows users to experiment with assembling a computer on their own. The target audience includes individuals with or without prior experience in computer assembly. The evaluation is conducted through pre-test and post-test in 2 areas: computer components and computer assembly. The results gathered from 10 participants showed that the significant result increasing from 10 to 14.2 out of 20 and also giving useful feedback for further development.
Keywords: Manufacturing Process and Optimization